Electrolytically removable adhesive composition, electrolytically removable adhesive sheet, and bonded body
Patent Information
- Application Number
- JP2026062018
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-04-04
- Filing Date
- 2026-04-03
- Publication Date
- 2026-10-16
AI Technical Summary
【0012】 本発明による電気剥離用接着剤組成物は、低湿度環境下においても電圧の印加により十分に接着力が低下する機能を発揮する。
Smart Images

Figure 2026169212000001_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to an adhesive composition for electric peeling, an electric peeling-type adhesive sheet, and a joined body.
BACKGROUND ART
[0002] In electronic component manufacturing processes, demands related to rework for yield improvement, recycling for disassembling and recovering components after use, and the like are increasing. To meet such demands, a double-sided electric peeling-type adhesive sheet having a certain peelability along with a certain adhesive force is sometimes used for bonding members together in electronic component manufacturing processes and the like.
[0003] As a double-sided adhesive sheet that achieves the above adhesive force and peelability, an adhesive sheet (electric peeling-type adhesive sheet) is known that uses an ionic liquid composed of a cation and an anion as a component forming the adhesive composition, and peels off by applying a voltage to the adhesive layer (Patent Documents 1 to 2).
[0004] In the electric peeling-type adhesive sheets of Patent Documents 1 to 2, application of a voltage causes the cation of the ionic liquid to move and reduction to occur on the cathode side, and the anion of the ionic liquid to move and oxidation to occur on the anode side. As a result, it is considered that the adhesive force at the adhesive interface is weakened and peeling is facilitated.
PRIOR ART DOCUMENTS
PATENT DOCUMENTS
[0005]
PATENT DOCUMENT 1
PATENT DOCUMENT 2
SUMMARY OF THE INVENTION
PROBLEMS TO BE SOLVED BY THE INVENTION
[0006] It is preferable that an electropenetrating adhesive sheet firmly bonds components when no voltage is applied, and can be peeled off with little force when voltage is applied. Therefore, it is preferable that the rate of decrease in adhesive strength due to voltage application is large in an electropenetrating adhesive sheet.
[0007] However, in environments with low humidity, such as during winter, the reduction in adhesive strength due to voltage application becomes smaller, which has been a problem.
[0008] The present invention has been completed in view of the above, and aims to provide an electropenetrating adhesive composition that can exhibit a function of sufficiently reducing adhesive strength by applying voltage even in a low humidity environment, and an electropenetrating adhesive sheet comprising an electropenetrating adhesive layer formed from the electropenetrating adhesive composition. [Means for solving the problem]
[0009] As a result of extensive research by the present inventors, it has been found that by creating an electro-removable adhesive composition comprising a polymer and two or more ionic substances, wherein the ionic substances include at least one specific ionic substance A, an electro-removable adhesive composition can be obtained in which the adhesive strength is sufficiently reduced by the application of voltage even in a low-humidity environment.
[0010] The means to solve the aforementioned problem are as follows: [1] It contains a polymer and two or more ionic substances, An electrolytic adhesive composition wherein the ionic substance contains at least one of the following ionic substances A. (Ionic substance A) An ionic substance comprising an anion and a cation, wherein the positive charge of the cation is located on an N element not included in the cyclic structure. [2] The electrolytic adhesive composition according to [1], wherein the ionic substance further contains at least one of the following ionic substances B. (Ionic substance B) An ionic substance that does not belong to the aforementioned ionic substance A. [3] The electrolytic adhesive composition according to [2], wherein the anion of the ionic substance B is at least one selected from the group consisting of bis(fluorosulfonyl)imide anion and bis(trifluoromethanesulfonyl)imide anion. [4] The electrolytic adhesive composition according to [2], wherein the content of the ionic substance A per 100 parts by mass of the polymer is 0.5 parts by mass or more, and the content of the ionic substance B is 0.5 parts by mass or more.
[0011] [5] An electropenetrating adhesive sheet comprising an adhesive layer formed from any one of the electropenetrating adhesive compositions described in [1] to [4]. [6] [5] comprises an adhesive sheet and an adherend having a conductive adhesive surface, A bonded body in which the adhesive layer is attached to the conductive surface to be bonded. [Effects of the Invention]
[0012] The electrolytic adhesive composition according to the present invention exhibits the function of sufficiently reducing adhesive strength upon application of voltage, even in low-humidity environments. [Brief explanation of the drawing]
[0013] [Figure 1] Figure 1 is a schematic cross-sectional view showing an example of the electropenetrating adhesive sheet of the present invention. [Figure 2] Figure 2 is a schematic cross-sectional view showing another example of the electropenetrating adhesive sheet of the present invention. [Figure 3] Figure 3 is a schematic cross-sectional view showing another example of the electropenetrating adhesive sheet of the present invention. [Figure 4] Figure 4 is a schematic cross-sectional view showing another example of the electropenetrating adhesive sheet of the present invention. [Figure 5] Figure 5 is a cross-sectional view illustrating the outline of the 180° peel test method in the example. [Modes for carrying out the invention]
[0014] The embodiments for carrying out the present invention will be described in detail below. However, the present invention is not limited to the embodiments described below. In this specification, "adhesive" is used to mean a tackling agent (also called a "pressure-sensitive adhesive").
[0015] [Electro-peelable adhesive sheet] [Structure of electropenetrating adhesive sheet] The electro-peelable adhesive sheet according to the embodiment of the present invention is not particularly limited in that it comprises an adhesive layer (electro-peelable adhesive layer) formed from an electro-peelable adhesive composition described later.
[0016] An electro-peelable adhesive sheet according to an embodiment of the present invention may contain only one electro-peelable adhesive layer, or it may contain two or more layers. An electro-peelable adhesive sheet according to an embodiment of the present invention may have adhesive layers other than the electro-peelable adhesive layer (hereinafter sometimes referred to as "other adhesive layers"). In addition to the above, an electro-peelable adhesive sheet according to an embodiment of the present invention may also have a substrate, a conductive layer, a conductive substrate, an intermediate layer, and a primer layer. The electro-peelable adhesive sheet according to the embodiment of the present invention may be in the form of a roll or a sheet, for example. The term "adhesive sheet" also includes the meaning of "adhesive tape." That is, the electro-peelable adhesive sheet according to the embodiment of the present invention may be an electro-peelable adhesive tape having a tape-like form.
[0017] An electro-peelable adhesive sheet according to an embodiment of the present invention may consist only of an adhesive layer without a substrate, i.e., a substrate-less double-sided adhesive sheet. An electro-peelable adhesive sheet according to an embodiment of the present invention may be a substrate-attached double-sided adhesive sheet having a substrate and adhesive layers (the electro-peelable adhesive layer of this embodiment and other adhesive layers) on both sides of the substrate. Alternatively, an electro-peelable adhesive sheet according to an embodiment of the present invention may be a substrate-attached single-sided adhesive sheet having a substrate and the electro-peelable adhesive layer of this embodiment on only one side of the substrate. An electro-peelable adhesive sheet according to an embodiment of the present invention may have a release liner for the purpose of protecting the surface of the adhesive layer, but such release liner is not included in the adhesive sheet of this embodiment.
[0018] An electro-peelable adhesive sheet according to an embodiment of the present invention comprises, in this order, a conductive substrate having at least one conductive surface, and an electro-peelable adhesive layer. The conductive surface of the conductive substrate and the electropenetrating adhesive layer are in contact. The aforementioned electropenetrating adhesive layer may be an adhesive sheet formed from an electropenetrating adhesive composition according to an embodiment of the present invention, as described later.
[0019] An electro-peelable adhesive sheet according to an embodiment of the present invention further comprises other adhesive layers, The adhesive sheet may have the other adhesive layer formed on the surface of the conductive substrate opposite to the electropenetrating adhesive layer.
[0020] Furthermore, the electropenetrating adhesive sheet according to the embodiment of the present invention further comprises another adhesive layer, a second conductive substrate, and a second other adhesive layer. The other adhesive layer is formed on the surface of the conductive substrate opposite to the electropenetrating adhesive layer. The second conductive substrate and the second other adhesive layer are formed in this order on the surface of the electropenetrating adhesive layer opposite to the conductive substrate. The adhesive sheet may be one in which the conductive surface of the second conductive substrate and the electropenetrating adhesive layer are in contact.
[0021] The structure of the electropenetrating adhesive sheet according to the embodiment of the present invention is not particularly limited, but the electropenetrating adhesive sheet X0 shown in Figure 1, the electropenetrating adhesive sheet X1 shown in Figure 2, the electropenetrating adhesive sheet X2 shown in Figure 3, and the electropenetrating adhesive sheet X3 shown in Figure 4 are preferred.
[0022] The electro-peelable adhesive sheet X0 shown in Figure 1 is a substrate-less double-sided electro-peelable adhesive sheet consisting only of an electro-peelable adhesive layer 1.
[0023] The electropenetrating adhesive sheet X1 shown in Figure 2 is a single-sided electropenetrating adhesive sheet with a substrate, having a layer structure consisting of an electropenetrating adhesive layer 1 and a conductive substrate 5 (a conductive layer 3 and a support substrate 4).
[0024] The electro-peelable adhesive sheet X2 shown in Figure 3 is a double-sided electro-peelable adhesive sheet with a substrate, having a layer structure consisting of another adhesive layer 6, a conductive substrate 5 (support substrate 4 and conductive layer 3), and an electro-peelable adhesive layer 1.
[0025] The electro-peelable adhesive sheet X3 shown in Figure 4 is an electro-peelable adhesive sheet having a layer structure comprising, in this order, other adhesive layer 6, conductive substrate 5 (support substrate 4, conductive layer 3), electro-peelable adhesive layer 1, conductive substrate 5 (conductive layer 3, support substrate 4), and other adhesive layer 6. That is, the electro-peelable adhesive layer 1 in the electro-peelable adhesive sheet X3 shown in Figure 4 is a double-sided electro-peelable adhesive sheet with a substrate, comprising the conductive layer 3, support substrate 4, and other adhesive layer 6 on both sides in this order. In the conductive substrate 5 of the electro-peelable adhesive sheets X1 to X3 shown in Figures 2 to 4, the support substrate 4 is not essential, and only the conductive layer 3 may be present.
[0026] The conductive layer 3 is not particularly limited as long as it is a conductive layer, but for example, it may be made from a conductive material such as metals such as aluminum, magnesium, copper, iron, niobium, titanium, chromium, nickel, tin, gold, or alloys mainly composed of these metals; an inorganic material such as a conductive metal oxide (e.g., ITO) or carbon (e.g., graphene); or a resin material such as a conductive polymer (e.g., a composite made of poly(3,4-ethylenedioxythiophene) and polystyrene sulfonic acid). The conductive layer 3 may have a single layer form or a multi-layer form. The conductive layer 3 is a layer formed from one or more of the conductive materials exemplified above. It is also possible that the conductive layer 3 is formed from a conductive composition in which the conductive material exemplified above is dispersed in a resin (for example, a conductive composition in which metal particles are dispersed in an epoxy resin). Alternatively, the conductive layer 3 may be a conductive layer provided on the support substrate 4. The method for forming the conductive layer 3 on the support substrate 4 is not particularly limited and can be set so that appropriate conductivity is exhibited on the surface of the support substrate 4. For example, the conductive layer 3 may be laminated on the surface of the support substrate 4 by methods such as plating, chemical vapor deposition, sputtering, conventional coating methods (for example, spray coating, roll coating, dip coating, etc.), or bonding using an adhesive.
[0027] The thickness of the conductive layer 3 is preferably 0.001 μm to 1000 μm, more preferably 0.001 μm to 500 μm, and even more preferably 0.01 μm to 300 μm, from the viewpoint of handling and processability. The thickness of the conductive layer 3 can be selected according to the intended use and usage conditions, i.e., the applied voltage conditions for peeling (whether peeling is desired with high voltage or low voltage), that is, the surface resistance value required for the conductive layer 3. For example, it may be 100 μm or less, 50 μm or less, 30 μm or less, 20 μm or less, 10 μm or less, 5 μm or less, 0.1 μm or less, or 0.05 μm or less.
[0028] The surface resistance of the conductive layer 3 is, for example, 1.0 × 10⁻⁶.4 Ω / □ or less, preferably 1.0 × 10 3 The resistance is less than or equal to Ω / □. The surface resistance can be calculated by dividing the resistivity measured by the four-terminal method in accordance with JIS K 7194 (1994) by the thickness of the conductive layer 3. Furthermore, the surface resistance of the conductive layer 3 can be selected according to the purpose and conditions of use, i.e., the applied voltage conditions for stripping (whether stripping is to be done with a high voltage or a low voltage). Lowering the surface resistance of the conductive layer 3 tends to lower the voltage required for stripping. For example, the surface resistance is 5.0 × 10 2 It can be less than or equal to Ω / □, and 1.0 × 10 2 It may be less than or equal to Ω / □, less than or equal to 50Ω / □, less than or equal to 40Ω / □, or less than or equal to 30Ω / □.
[0029] The supporting substrate 4 is not particularly limited, but examples include paper-based substrates such as paper; fiber-based substrates such as cloth and nonwoven fabrics; plastic-based substrates such as films and sheets mainly composed of various plastics (e.g., polyolefin resins such as polyethylene and polypropylene, polyester resins such as polyethylene terephthalate, and acrylic resins such as polymethyl methacrylate); foam substrates made of foams of various plastics (polyolefin resins such as polyethylene, polypropylene, ethylene-propylene copolymer polymer, and ethylene-vinyl acetate copolymer polymer, polyurethane resins, rubber resins such as acrylic rubber and other elastomers); and laminates thereof. The substrate may have a single layer or a multi-layer form. The substrate may be subjected to various treatments such as back treatment, antistatic treatment, and primer treatment as needed.
[0030] The thickness of the support substrate 4 is preferably 2 μm to 1000 μm, more preferably 2 μm to 500 μm, and even more preferably 5 μm to 300 μm, from the viewpoint of handling and processability. The thickness of the support substrate 4 can be selected according to the purpose and manner of use. For example, it may be 150 μm or less, 100 μm or less, 70 μm or less, 50 μm or less, 40 μm or less, or 30 μm or less. When the thickness of the support substrate 4 is reduced, the conformability of the adhesive sheet to the surface shape of the adherend tends to improve. Also, from the viewpoint of handling and processability, the thickness of the substrate may be, for example, 10 μm or more, 12 μm or more, 15 μm or more, or 20 μm or more.
[0031] The conductive substrate 5 is not particularly limited as long as it is a substrate on which at least one surface is conductive (conducts electricity). It may be a single layer or a laminated structure of conductive material. That is, it may be a conductive substrate consisting only of the conductive layer 3. The description of conductive materials that can be used for the conductive layer 3 above can be directly applied to the conductive material. If the conductive substrate 5 includes a support substrate 4 and a conductive layer 3, the conductive substrate 5 may be a support substrate 4 with the conductive layer 3 formed on its surface, etc.
[0032] An electropenetrating adhesive sheet according to an embodiment of the present invention may further comprise a coating layer. The coating layer can be provided between the electropenetrating adhesive layer 1 and the conductive layer 3. The electropenetrating adhesive sheet according to the embodiment of the present invention further comprises a coating layer, which acts as a barrier preventing ionic substances contained in the electropenetrating adhesive layer 1 from penetrating into the conductive layer 3 when a voltage is applied, thereby preventing the conductive layer 3 from peeling off from the supporting substrate 4. Furthermore, the contact between the coating layer and the electrorelease adhesive layer 1 improves the adhesion between the electrorelease adhesive layer 1 and the conductive layer 3, preventing the interfacial adhesion between the electrorelease adhesive layer 1 and the conductive substrate 5 from decreasing and peeling off within the adhesive sheet due to thermal curing of the electrorelease adhesive layer 1 when exposed to a high-temperature environment.
[0033] The coating layer is a layer mainly composed of resin or inorganic material, and can be formed from a resin composition mainly composed of resin components or a composition mainly composed of inorganic material. The coating layer is made of at least one resin selected from polyester resins, acrylic resins, epoxy resins, urethane resins, or SiN x SiO x Preferably, it contains at least one inorganic substance selected from Al2O3, Ni, NiCr, and carbon.
[0034] The thickness of the conductive substrate 5 is preferably 2 μm or more and 1000 μm or less, more preferably 2 μm or more and 500 μm or less, and even more preferably 5 μm or more and 300 μm or less. The thickness of the conductive substrate 5 can be selected according to the purpose of use and the manner of use. For example, it may be 150 μm or less, 100 μm or less, 70 μm or less, 50 μm or less, 40 μm or less, or 30 μm or less. When the thickness of the conductive substrate 5 is reduced, the conformability of the adhesive sheet to the surface shape of the adherend tends to improve. Also, from the viewpoint of handling and processability, the thickness of the substrate may be, for example, 10 μm or more, 12 μm or more, 15 μm or more, or 20 μm or more.
[0035] An electropenetrating adhesive sheet according to an embodiment of the present invention can be attached to an object having a conductive adhesive surface to form a bonded body. The surface resistance of the conductive substrate to which the electropenetrating adhesive sheet is attached is, for example, 1.0 × 10⁻⁶. 4 Ω / □ or less, preferably 1.0 × 10 3Ω / sq or less. The surface resistance value can be calculated by dividing the resistivity measured by the 4-probe method in accordance with JIS K 7194 (1994) by the thickness of the conductive deposited surface (i.e., the conductive material). In addition, the surface resistance value of the conductive deposited surface can be selected as required according to the purpose of use and use conditions, that is, the applied voltage condition for peeling (whether peeling is desired at a high voltage or at a low voltage). When the surface resistance value of the conductive deposited surface is lowered, the voltage required for peeling tends to decrease. For example, the surface resistance value is 5.0×10 2 Ω / sq or less, or 1.0×10 2 Ω / sq or less, 50Ω / sq or less, 40Ω / sq or less, or 30Ω / sq or less.
[0036] Examples of the adherend having a conductive deposited surface include a conductive substrate and a substrate having a conductive layer. The conductive substrate may be a single layer or a laminate of conductive materials. As the conductive material, the above description of the conductive material that can be used for the conductive layer 3 can be directly incorporated herein by reference. The substrate having a conductive layer may be one obtained by forming the above-mentioned conductive material on the surface of a base material. The method for forming the conductive material on the base material is not particularly limited, and can be set so that appropriate conductivity is exhibited on the surface of the base material. For example, the conductive material may be laminated by a plating method, a chemical vapor deposition method, a sputtering method, a conventional coating method (e.g., a spray coating method, a roll coating method, a dip coating method, etc.), lamination using an adhesive, or the like. The base material may be the above-mentioned conductive base material, or may be a non-conductive base material.
[0037] The non-conductive substrate is not particularly limited, but examples include paper-based substrates such as paper; fiber-based substrates such as cloth and nonwoven fabric; substrates mainly composed of various plastics (e.g., polyolefin resins such as polyethylene and polypropylene, polyester resins such as polyethylene terephthalate, acrylic resins such as polymethyl methacrylate, polyimide resins, etc.); plastic substrates such as housings; glass substrates; and laminates thereof. The substrate may have a single-layer form or a multi-layer form. The substrate may be subjected to various treatments as needed, such as rust prevention treatment, back treatment, antistatic treatment, and primer treatment.
[0038] The electropenetrating adhesive layer 1 is an adhesive layer that has the property of decreasing adhesive strength when a voltage is applied. The electropenetrating adhesive layer contains a polymer acting as an adhesive and ionic substance A, which is an ionic substance. Here, "ionic substance" is a general term for substances composed of at least one pair of anions and cations. Regardless of its form, it refers to a substance that ionizes in the polymer, in solution, in a liquid state, or in a solid state and exhibits electrical conductivity. In this specification, when simply referred to as "ionic substance," it includes ionic substance A and ionic substances other than ionic substance A (ionic substance B, described later).
[0039] Ionic substances at room temperature (25°C) can be in any state other than gas. That is, ionic substances may be solids, liquids, or intermediate states between solid and liquid (e.g., liquid crystals, viscous crystals, viscous solids, viscous liquids) at room temperature (25°C). The state of an ionic substance at room temperature (25°C) depends on its molecular structure. For example, ionic liquids are compounds composed of cations and anions that have a melting point below room temperature (25°C) and are liquid at room temperature, such as 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide. Ionic solids are substances that have a melting point above 25°C and are ionic, such as metal salts (e.g., sodium chloride and copper sulfate) and high-melting-point organic ionic solids (e.g., 1-ethyl-3-methylimidazolium bromide and 1-ethyl-1-methylpiperidinium iodide).
[0040] The electropenetrating adhesive layer 1 can be formed by an electropenetrating adhesive composition comprising a polymer and two or more ionic substances, wherein the ionic substances contain at least one specific ionic substance A. The electropenetrating adhesive compositions according to embodiments of the present invention will be described below.
[0041] In this specification, the adhesive strength when no voltage is applied may be referred to as "initial adhesive strength." Furthermore, the property of adhesive strength decreasing due to the application of voltage is called "electropenetration," and a large decrease in adhesive strength due to voltage application is sometimes described as "excellent electropenetration." Also, the adhesive strength after voltage application is sometimes called "electropenetration force."
[0042] [Components of electrolytic adhesive compositions] An electrolytic adhesive composition according to an embodiment of the present invention comprises a polymer and two or more ionic substances, wherein the ionic substances contain at least one of the following ionic substances A. (Ionic substance A) An ionic substance comprising an anion and a cation, wherein the positive charge of the cation is located on an N element not included in the cyclic structure.
[0043] (polymer) The electrolytic adhesive composition according to the embodiment of the present invention contains a polymer. In this embodiment, the polymer is not particularly limited as long as it is a general organic polymer compound, for example, a monomer polymer or partial polymer. The monomer may be a single monomer or a mixture of two or more monomers. A partial polymer means a polymer in which at least a portion of the monomer or monomer mixture is partially polymerized.
[0044] The polymer in this embodiment is not particularly limited as long as it is commonly used as an adhesive and has adhesive properties, but examples include acrylic polymers, rubber polymers, vinyl alkyl ether polymers, silicone polymers, polyester polymers, polyamide polymers, urethane polymers, fluoropolymers, and epoxy polymers. The polymers can be used alone or in combination of two or more types. In order to increase the dielectric constant of components other than ionic substances in the resulting electropeelable adhesive layer and improve electropeelability, it is preferable that the polymer has a high dielectric constant. From this viewpoint, it is particularly preferable that the polymer in this embodiment includes at least one selected from the group consisting of polyester polymers and acrylic polymers having carboxyl groups and / or hydroxyl groups. Since polyester polymers have easily polarizable hydroxyl groups at their ends, and since acrylic polymers having carboxyl groups and / or hydroxyl groups have easily polarizable carboxyl groups and / or hydroxyl groups, using these polymers makes it possible to obtain a polymer with a relatively high dielectric constant. The total content of polyester polymers and acrylic polymers having carboxyl groups and / or hydroxyl groups in the polymer according to the embodiment of the present invention is preferably 60% by mass or more, and more preferably 80% by mass or more. Furthermore, in order to increase cost, productivity, and initial adhesive strength, it is preferable that the polymer in this embodiment be an acrylic polymer. In other words, the electrolytic adhesive composition according to the embodiment of the present invention is preferably an acrylic electrolytic adhesive composition containing an acrylic polymer as the polymer.
[0045] The acrylic polymer preferably contains monomer units derived from alkyl (meth)acrylate esters having an alkyl group with 1 to 14 carbon atoms (formula (1) below). Such monomer units are suitable for obtaining high initial adhesion. Furthermore, to increase the dielectric constant of components other than ionic substances in the electropenetrating adhesive layer and improve electropenetration, the alkyl group R in formula (1) below is preferable. b The number of carbon atoms is preferably small, particularly preferably 8 or less, and more preferably 4 or less. CH2=C(R a )COOR b (1) [R in equation (1) a R is a hydrogen atom or a methyl group, b [This is an alkyl group having 1 to 14 carbon atoms, which may have substituents.]
[0046] Examples of alkyl (meth)acrylate esters having an alkyl group with 1 to 14 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, 1,3-dimethylbutyl acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, and 2-ethylbutyl (meth)acrylate. Examples include lylate, heptyl(meth)acrylate, n-octyl(meth)acrylate, isooctyl(meth)acrylate, 2-ethylhexyl(meth)acrylate, n-nonyl(meth)acrylate, isononyl(meth)acrylate, n-decyl(meth)acrylate, isodecyl(meth)acrylate, n-dodecyl(meth)acrylate, n-tridecyl(meth)acrylate, n-tetradecyl(meth)acrylate, and 2-methoxyethyl acrylate. Among these, n-butyl acrylate, 2-ethylhexyl acrylate, isononyl acrylate, and 2-methoxyethyl acrylate are preferred. Alkyl (meth)acrylate esters having an alkyl group with 1 to 14 carbon atoms can be used alone or in combination of two or more.
[0047] The proportion of alkyl (meth)acrylate ester having an alkyl group with 1 to 14 carbon atoms relative to the total monomer components (100% by mass) constituting the acrylic polymer is not particularly limited, but is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 85% by mass or more. When the proportion of alkyl (meth)acrylate ester having an alkyl group with 1 to 14 carbon atoms is 70% by mass or more, it is easier to obtain a large initial adhesive strength.
[0048] As an acrylic polymer, it is preferable to include monomer units derived from (meth)acrylate alkyl esters having alkyl groups with 1 to 14 carbon atoms, as well as monomer units derived from polar group-containing monomers copolymerizable thereto, for the purpose of modifying cohesive strength, heat resistance, crosslinkability, etc. Such monomer units can provide crosslinking sites and are suitable for obtaining high initial adhesion. Furthermore, from the viewpoint of increasing the dielectric constant of components other than ionic substances in the electropenetrating adhesive layer and improving electropenetration, it is also preferable to include monomer units derived from polar group-containing monomers.
[0049] Examples of polar group-containing monomers include carboxyl group-containing monomers, hydroxyl group-containing monomers, cyano group-containing monomers, vinyl group-containing monomers, aromatic vinyl monomers, amide group-containing monomers, imide group-containing monomers, amino group-containing monomers, epoxy group-containing monomers, vinyl ether monomers, N-acryloylmorpholine, sulfo group-containing monomers, phosphate group-containing monomers, and acid anhydride group-containing monomers. Among these, carboxyl group-containing monomers, hydroxyl group-containing monomers, and amide group-containing monomers are preferred due to their excellent cohesiveness, and carboxyl group-containing monomers are particularly preferred. Carboxyl group-containing monomers are especially suitable for obtaining high initial adhesion. Polar group-containing monomers can be used alone or in combination of two or more types.
[0050] Examples of carboxyl group-containing monomers include acrylic acid, methacrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid. Acrylic acid is particularly preferred. Carboxyl group-containing monomers can be used alone or in combination of two or more.
[0051] Examples of hydroxyl group-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, (4-hydroxymethylcyclohexyl)methyl (meth)acrylate, N-methylol (meth)acrylamide, vinyl alcohol, allyl alcohol, 2-hydroxyethyl vinyl ether, 4-hydroxybutyl vinyl ether, and diethylene glycol monovinyl ether. 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are particularly preferred. Hydroxyl group-containing monomers can be used individually or in combination of two or more.
[0052] Examples of amide group-containing monomers include acrylamide, methacrylamide, N-vinylpyrrolidone, N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N,N-diethylacrylamide, N,N-diethylmethacrylamide, N,N'-methylenebisacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethacrylamide, and diacetoneacrylamide. Amide group-containing monomers can be used alone or in combination of two or more.
[0053] Examples of cyano group-containing monomers include acrylonitrile and methacrylonitrile.
[0054] Examples of vinyl group-containing monomers include vinyl acetate, vinyl propionate, and vinyl esters such as vinyl laurate, with vinyl acetate being particularly preferred.
[0055] Examples of aromatic vinyl monomers include styrene, chlorostyrene, chloromethylstyrene, α-methylstyrene, and other substituted styrenes.
[0056] Examples of imide group-containing monomers include cyclohexylmaleimide, isopropylmaleimide, N-cyclohexylmaleimide, and itaconimide.
[0057] Examples of amino group-containing monomers include aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, and N,N-dimethylaminopropyl (meth)acrylate.
[0058] Examples of epoxy group-containing monomers include glycidyl (meth)acrylate, methylglycidyl (meth)acrylate, and allyl glycidyl ether.
[0059] Examples of vinyl ether monomers include methyl vinyl ether, ethyl vinyl ether, and isobutyl vinyl ether.
[0060] The proportion of polar group-containing monomers to the total monomer components (100% by mass) constituting the acrylic polymer is preferably 0.1% by mass or more and 35% by mass or less. The upper limit of the proportion of polar group-containing monomers is more preferably 25% by mass, even more preferably 20% by mass, the lower limit is more preferably 0.5% by mass, even more preferably 1% by mass, and particularly preferably 2% by mass. When the proportion of polar group-containing monomers is 0.1% by mass or more, cohesive force is easily obtained, so adhesive residue is less likely to occur on the surface of the adherend after peeling off the electrorelease adhesive layer, and electrorelease properties are improved. Furthermore, when the proportion of polar group-containing monomers is 35% by mass or less, it becomes easier to prevent the electrorelease adhesive layer from adhering excessively to the adherend and causing excessive peeling. In particular, when it is 2% by mass or more and 20% by mass or less, it becomes easier to achieve both peelability to the adherend and adhesion between the electrorelease adhesive layer and the conductive layer.
[0061] Furthermore, the monomer components constituting the acrylic polymer may include polyfunctional monomers in order to introduce a cross-linked structure into the acrylic polymer and facilitate obtaining the necessary cohesive force.
[0062] Examples of polyfunctional monomers include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, divinylbenzene, and N,N'-methylenebisacrylamide. Polyfunctional monomers can be used individually or in combination of two or more.
[0063] The content of polyfunctional monomers relative to the total monomer components (100% by mass) constituting the acrylic polymer is preferably 0.1% by mass or more and 15% by mass or less. The upper limit of the polyfunctional monomer content is more preferably 10% by mass, and the lower limit is more preferably 3% by mass. A polyfunctional monomer content of 0.1% by mass or more is preferable because it tends to improve the flexibility and adhesion of the electropenetrating adhesive layer. A polyfunctional monomer content of 15% by mass or less makes it easier to obtain appropriate adhesion without the cohesive force becoming too high.
[0064] Polyester polymers are typically polymers having a structure in which polycarboxylic acids such as dicarboxylic acids or their derivatives (hereinafter also referred to as "polycarboxylic acid monomers") and polyhydric alcohols such as diols or their derivatives (hereinafter referred to as "polyhydric alcohol monomers") are condensed together.
[0065] The polycarboxylic acid monomer is not particularly limited, but examples include adipic acid, azelaic acid, dimer acid, sebacic acid, 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 4-methyl-1,2-cyclohexanedicarboxylic acid, dodecenyl succinic anhydride, fumaric acid, succinic acid, dodecanediic acid, hexahydrophthalic anhydride, tetrahydrophthalic anhydride, maleic acid, maleic anhydride, itaconic acid, citraconic acid, and derivatives thereof. Polycarboxylic acid monomers can be used individually or in combination of two or more types.
[0066] The polyhydric alcohol monomer is not particularly limited, but examples include ethylene glycol, 1,2-propylene glycol, 1,3-propanediol, 2-methyl-1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, diethylene glycol, dipropylene glycol, 2,2,4-trimethyl-1,5-pentanediol, 2-ethyl-2-butylpropanediol, 1,9-nonanediol, 2-methyloctanediol, 1,10-decanediol, and derivatives thereof. Polyhydric alcohol monomers can be used alone or in combination of two or more types.
[0067] Furthermore, the polymer according to the embodiment of the present invention may also contain an ionic polymer. An ionic polymer is a polymer having an ionic functional group. The inclusion of an ionic polymer in the polymer increases the dielectric constant of the polymer and improves its electrolytic properties. When the polymer contains an ionic polymer, the content of the ionic polymer is preferably 0.05 parts by mass or more and 2 parts by mass or less per 100 parts by mass of the polymer.
[0068] In this embodiment, the polymer can be obtained by (co)polymerizing monomer components. The polymerization method is not particularly limited, but examples include solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, and photopolymerization (active energy ray polymerization). Solution polymerization is particularly preferred from the viewpoint of cost and productivity. When copolymerized, the polymer may be a random copolymer, block copolymer, alternating copolymer, graft copolymer, etc.
[0069] Solution polymerization methods are not particularly limited, but include methods in which monomer components, polymerization initiators, etc., are dissolved in a solvent, heated to polymerize, and a polymer solution containing the polymer is obtained.
[0070] Various common solvents can be used as solvents in solution polymerization. Examples of such solvents (polymerization solvents) include aromatic hydrocarbons such as toluene, benzene, and xylene; esters such as ethyl acetate and n-butyl acetate; aliphatic hydrocarbons such as n-hexane and n-heptane; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; and organic solvents such as ketones such as methyl ethyl ketone and methyl isobutyl ketone. Solvents can be used individually or in combination of two or more.
[0071] The amount of solvent used is not particularly limited, but is preferably 10 parts by mass or more and 1000 parts by mass or less relative to the total monomer components constituting the polymer (100 parts by mass). The upper limit of the amount of solvent used is more preferably 500 parts by mass, and the lower limit is more preferably 50 parts by mass.
[0072] Polymerization initiators used in solution polymerization are not particularly limited, but include peroxide-based polymerization initiators and azo-based polymerization initiators. Peroxide-based polymerization initiators are not particularly limited, but include peroxycarbonates, ketone peroxides, peroxyketals, hydroperoxides, dialkyl peroxides, diacyl peroxides, and peroxyesters. More specifically, examples include benzoyl peroxide, t-butyl hydroperoxide, di-t-butyl peroxide, t-butyl peroxybenzoate, dicumyl peroxide, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, and 1,1-bis(t-butylperoxy)cyclododecane. Azo polymerization initiators are not particularly limited, but include 2,2'-azobisisobutyronitrile, 2,2'-azobis-2-methylbutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylpropionic acid)dimethyl, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 1,1'-azobis(cyclohexane-1-carbonitride), 2,2'-azobis(2,4,4-trimethylpentane), and 4,4'-azobi Examples include s-4-cyanovaleric acid, 2,2'-azobis(2-amidinopropane)dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane]dihydrochloride, 2,2'-azobis(2-methylpropionamidine)disulfate, 2,2'-azobis(N,N'-dimethyleneisobutylamidine)hydrochloride, and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]hydrate. Polymerization initiators can be used alone or in combination of two or more.
[0073] The amount of polymerization initiator used is not particularly limited, but it is preferably 0.01 parts by mass or more and 5 parts by mass or less relative to the total monomer components constituting the polymer (100 parts by mass). The upper limit of the amount of polymerization initiator used is more preferably 3 parts by mass, and the lower limit is more preferably 0.05 parts by mass.
[0074] In solution polymerization, the heating temperature during polymerization is not particularly limited, but is, for example, between 50°C and 80°C. The heating time is not particularly limited, but is, for example, between 1 hour and 24 hours.
[0075] The weight-average molecular weight of the polymer is not particularly limited, but is preferably between 100,000 and 5,000,000. The upper limit of the weight-average molecular weight is more preferably 4,000,000, even more preferably 3,000,000, and the lower limit is more preferably 200,000, even more preferably 300,000. When the weight-average molecular weight is 100,000 or more, the cohesive force is reduced, which effectively suppresses the problem of adhesive residue remaining on the surface of the adherend after the electro-release adhesive layer has been removed. Furthermore, when the weight-average molecular weight is 5,000,000 or less, it effectively suppresses the problem of insufficient wettability on the surface of the adherend after the electro-release adhesive layer has been removed.
[0076] The weight-average molecular weight was obtained by measuring using gel permeation chromatography (GPC). More specifically, for example, it can be measured using the "HLC-8220GPC" (manufactured by Tosoh Corporation) GPC measuring device under the following conditions and calculated using the standard polystyrene equivalent value. (Weight average molecular weight measurement conditions) • Sample concentration: 0.2% by mass (tetrahydrofuran solution) • Sample injection volume: 10 μL • Sample columns: TSKguardcolumn SuperHZ-H (1 tube) + TSKgel SuperHZM-H (2 tubes) • Reference column: TSKgel SuperH-RC (1 tube) • Eluent: Tetrahydrofuran (THF) ·Flow rate: 0.6mL / min • Detector: Differential refractometer (RI) • Column temperature (measurement temperature): 40°C
[0077] The glass transition temperature (Tg) of the polymer is not particularly limited, but it is preferably 0°C or lower because it suppresses the decrease in initial adhesive strength, more preferably -10°C or lower, and even more preferably -20°C or lower. Furthermore, it is particularly preferable to have a temperature of -40°C or lower because the rate of decrease in adhesive strength due to voltage application is particularly large, and most preferably -50°C or lower.
[0078] The glass transition temperature (Tg) can be calculated, for example, based on the following equation (Y) (Fox equation). 1 / Tg=W1 / Tg1+W2 / Tg2++Wn / Tgn (Y) [In equation (Y), Tg is the glass transition temperature of the polymer (unit: K), Tgi(i=1, 2, ...n) is the glass transition temperature when monomer i forms a homopolymer (unit: K), and Wi(i=1, 2, ...n) represents the mass fraction of monomer i in the total monomer components.] The above formula (Y) is the calculation formula when the polymer is composed of n types of monomer components: monomer 1, monomer 2, ..., monomer n.
[0079] The glass transition temperature when forming a homopolymer refers to the glass transition temperature of the homopolymer of the monomer in question, and specifically refers to the glass transition temperature (Tg) of a polymer formed using only one monomer (sometimes referred to as "monomer X") as the monomer component. The specific values are given in the "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1989). For homopolymers not listed in the aforementioned literature, the glass transition temperature (Tg) refers to a value obtained, for example, by the following measurement method: In a reactor equipped with a thermometer, stirrer, nitrogen inlet tube, and reflux condenser, 100 parts by mass of monomer X, 0.2 parts by mass of 2,2'-azobisisobutyronitrile, and 200 parts by mass of ethyl acetate as a polymerization solvent are added, and the mixture is stirred for 1 hour while introducing nitrogen gas. After removing oxygen from the polymerization system in this manner, the temperature is raised to 63°C and the reaction is carried out for 10 hours. Then, the mixture is cooled to room temperature to obtain a homopolymer solution with a solid content of 33% by mass. Next, this homopolymer solution is cast onto a release liner and dried to prepare a test sample (sheet-like homopolymer) with a thickness of approximately 2 mm. Then, approximately 1-2 mg of this test sample is weighed into an aluminum open cell, and the reversing heat flow (specific heat component) behavior of the homopolymer is obtained using a temperature-modulated DSC (product name "Q-2000", manufactured by T.A. Instruments) at a heating rate of 5°C / min under a nitrogen atmosphere of 50 ml / min. Referring to JIS K 7121 (2012), the glass transition temperature (Tg) of the homopolymer is defined as the temperature at the point where a line equidistant in the vertical axis direction from the line extending from the low-temperature baseline and high-temperature baseline of the obtained reversing heat flow intersects with the curve of the step-like change portion of the glass transition.
[0080] The polymer content in the electrolytic adhesive composition according to the embodiment of the present invention is preferably 50% by mass or more and 99.9% by mass or less, based on the total amount (100% by mass) of the electrolytic adhesive composition, with the upper limit being more preferably 99.5% by mass, even more preferably 99% by mass, and the lower limit being more preferably 60% by mass, even more preferably 70% by mass.
[0081] (Ionic substances) The electrolytic adhesive composition according to the embodiment of the present invention contains an ionic substance that includes electrically charged molecules (ions).
[0082] An electrolytic adhesive composition according to an embodiment of the present invention more specifically comprises two or more ionic substances, wherein each ionic substance contains at least one ionic substance A. Here, ionic substance A refers to an ionic substance comprising anions and cations, wherein the positive charge of the cation is located on an N element not included in the cyclic structure. If an electrolytic adhesive composition contains only one ionic substance, or if the ionic substance does not contain at least one ionic substance A, the function of reducing adhesive strength upon application of voltage may not be exhibited in low-humidity environments.
[0083] When an ionic substance has two or more positive charges, the positive charges of the cations in ionic substance A are all located on the N element, which is not included in the cyclic structure.
[0084] The anion of ionic substance A is, for example, (FSO2)2N - , (CF3SO2)2N - , (CF3CF2SO2)2N - (CF3SO2)3C - , Br - AlCl4 - Al2Cl7 - NO3 - BF4 - PF6 - CH3COO - CF3COO - , CF3CF2CF2COO - CF3SO3 - CF3(CF2)3SO3 - AsF6 - SbF6 - , and F(HF) n - These are some examples. Among them, as an anion, (FSO2)2N -[Bis(fluorosulfonyl)imido anion] and (CF3SO2)2N - Anions of sulfonylime compounds such as [bis(trifluoromethanesulfonyl)imide anion] are preferred because they are chemically stable and provide good electrolytic properties. In other words, it is preferable that the anion of ionic substance A is at least one selected from the group consisting of bis(fluorosulfonyl)imide anions and bis(trifluoromethanesulfonyl)imide anions.
[0085] In ionic substance A, nitrogen-containing onium cations are preferred because they are chemically stable and suitable for improving electrolysis, and ammonium-based cations are more preferred.
[0086] Examples of ammonium-based cations include tetraethylammonium cation, tetrabutylammonium cation, methyltrioctylammonium cation, tetradecyltrihexylammonium cation, glycidyltrimethylammonium cation, trimethylaminoethyl acrylate cation, diallyldimethylammonium cation, dodecyltrimethylammonium cation, tributylmethylammonium cation, benzyldimethyldodecylammonium cation, benzyldimethyltetradecylammonium cation, benzyldimethylhexadecylammonium cation and dodecylethyldimethylammonium cation, benzyltributylammonium cation, triethylpentylammonium cation, trimethylbutylammonium cation, diethyl(2-methoxyethyl)methylammonium cation, and diethylmethylpropylammonium cation.
[0087] As for ionic substance A, from the viewpoint of significantly reducing the rate of decrease in adhesive strength when voltage is applied, it is preferable to select a cation with a molecular weight of 200 or less as the constituent cation, such as (FSO2)2N. - [Bis(fluorosulfonyl)imido anion] or (CF3SO2)2N -Ionic substances containing [bis(trifluoromethanesulfonyl)imide anion] and a cation with a molecular weight of 200 or less are particularly preferred. Examples of cations with a molecular weight of 200 or less include diallyldimethylammonium cation, tributylmethylammonium cation, triethylpentylammonium cation, trimethylbutylammonium cation, diethyl(2-methoxyethyl)methylammonium, tetraethylammonium cation, glycidyltrimethylammonium cation, and trimethylaminoethyl acrylate cation.
[0088] Furthermore, the cation of ionic substance A can also be represented by the following formula.
[0089] [ka]
[0090] R in the above formula 102 , R 103 , R 104 , and R 105 These represent, either identically or differently, hydrocarbon groups having 1 to 16 carbon atoms (preferably hydrocarbon groups having 1 to 14 carbon atoms, more preferably hydrocarbon groups having 1 to 10 carbon atoms, even more preferably hydrocarbon groups having 1 to 8 carbon atoms, and particularly preferably hydrocarbon groups having 1 to 6 carbon atoms), and may also contain heteroatoms.
[0091] The molecular weight of the cation in ionic substance A is, for example, 500 or less, preferably 400 or less, more preferably 300 or less, even more preferably 250 or less, and particularly preferably 200 or less. It is also usually 50 or more. It is believed that the cation in the ionic substance has the property of moving towards the cathode side when a voltage is applied in the electropenetrating adhesive layer, and becoming concentrated near the interface between the electropenetrating adhesive layer and the adherend. In the embodiments of the present invention, this results in a decrease in adhesive strength after voltage application compared to the initial adhesive strength, and electropenetration occurs. Cationic substances with small molecular weights, such as 500 or less, are preferable from the viewpoint of facilitating the movement of cations towards the cathode side in the electropenetrating adhesive layer, and thus facilitating the realization of the function of decreasing adhesive strength upon voltage application.
[0092] Ionic substance A may be a commercially available product, but it can also be synthesized as described below. The synthesis method for ionic substance A is not particularly limited as long as the desired ionic substance is obtained, but generally, methods such as the halide method, hydroxide method, acid ester method, complex formation method, and neutralization method are used, as described in the literature “Ionic Liquids - The Forefront and Future of Development -” [published by CMC Publishing Co., Ltd.].
[0093] The following describes the synthesis methods of nitrogen-containing onium salts using the halide method, hydroxide method, acid ester method, complex formation method, and neutralization method, but other ionic substances such as sulfur-containing onium salts and phosphorus-containing onium salts, as well as ionic substance B described later, can be obtained by similar methods.
[0094] In the electro-peelable adhesive composition according to the embodiment of the present invention, the content (amount blended) of ionic substance A is preferably 0.5 parts by mass or more per 100 parts by mass of polymer from the viewpoint of reducing the adhesive strength after voltage application, and preferably 30 parts by mass or less from the viewpoint of increasing the initial adhesive strength. From the same viewpoint, it is more preferably 20 parts by mass or less, even more preferably 15 parts by mass or less, particularly preferably 10 parts by mass or less, and most preferably 5 parts by mass or less. Furthermore, it is more preferably 0.6 parts by mass or more, even more preferably 0.8 parts by mass or more, particularly preferably 1.0 part by mass or more, and most preferably 1.5 parts by mass or more.
[0095] The electrolytic adhesive composition according to the embodiment of the present invention may further contain at least one of the following ionic substances B. (Ionic substance B) An ionic substance that does not belong to the aforementioned ionic substance A.
[0096] The anion of ionic substance B is, for example, (FSO2)2N - , (CF3SO2)2N - , (CF3CF2SO2)2N - (CF3SO2)3C - , Br - AlCl4 - Al2Cl7 - NO3 - BF4 - PF6 - CH3COO - CF3COO - , CF3CF2CF2COO - CF3SO3 - CF3(CF2)3SO3 - AsF6 - SbF6 - , and F(HF) n - These are some examples. Among them, as an anion, (FSO2)2N - [Bis(fluorosulfonyl)imido anion] and (CF3SO2)2N -Anions of sulfonylime compounds such as [bis(trifluoromethanesulfonyl)imide anion] are preferred because they are chemically stable and provide good electrolytic properties. In other words, the anion of ionic substance B is preferably at least one selected from the group consisting of bis(fluorosulfonyl)imide anion and bis(trifluoromethanesulfonyl)imide anion.
[0097] The cation in ionic substance B is preferably at least one selected from the group consisting of nitrogen-containing onium cations, sulfur-containing onium cations, and phosphorus-containing onium cations, in order to be chemically stable and to have good electrolytic properties, and imidazolium-based, pyrrolidinium-based, and pyridinium-based cations are more preferred.
[0098] Examples of imidazolium-based cations include 1-methylimidazolium cation, 1-ethyl-3-methylimidazolium cation, 1-propyl-3-methylimidazolium cation, 1-butyl-3-methylimidazolium cation, 1-pentyl-3-methylimidazolium cation, 1-hexyl-3-methylimidazolium cation, 1-heptyl-3-methylimidazolium cation, 1-octyl-3-methylimidazolium cation, 1-nonyl-3-methylimidazolium cation, 1-undecyl-3-methylimidazolium cation, and 1-dodecyl-3-methylimidazolium cation. Examples include 1-tridecyl-3-methylimidazolium cation, 1-tetradecyl-3-methylimidazolium cation, 1-pentadecyl-3-methylimidazolium cation, 1-hexadecyl-3-methylimidazolium cation, 1-heptadecyl-3-methylimidazolium cation, 1-octadecyl-3-methylimidazolium cation, 1-undecyl-3-methylimidazolium cation, 1-benzyl-3-methylimidazolium cation, 1-butyl-2,3-dimethylimidazolium cation, and 1,3-bis(dodecyl)imidazolium cation.
[0099] Examples of pyridinium-based cations include 1-butylpyridinium cation, 1-hexylpyridinium cation, 1-butyl-3-methylpyridinium cation, 1-butyl-4-methylpyridinium cation, and 1-octyl-4-methylpyridinium cation.
[0100] Examples of pyrrolidinium-based cations include 1-ethyl-1-methylpyrrolidinium cation and 1-butyl-1-methylpyrrolidinium cation.
[0101] As for ionic substance B, from the viewpoint of significantly reducing the rate of decrease in adhesive strength when voltage is applied, it is preferable to select a cation with a molecular weight of 160 or less as the constituent cation, as shown above (FSO2)2N - [Bis(fluorosulfonyl)imido anion] or (CF3SO2)2N - An ionic substance containing a [bis(trifluoromethanesulfonyl)imide anion] and a cation with a molecular weight of 160 or less is particularly preferred. Examples of cations with a molecular weight of 160 or less include 1-methylimidazolium cation, 1-ethyl-3-methylimidazolium cation, 1-propyl-3-methylimidazolium cation, 1-butyl-3-methylimidazolium cation, 1-pentyl-3-methylimidazolium cation, 1-butylpyridinium cation, 1-hexylpyridinium cation, 1-butyl-3-methylpyridinium cation, 1-butyl-4-methylpyridinium cation, 1-ethyl-1-methylpyrrolidinium cation, and 1-butyl-1-methylpyrrolidinium cation.
[0102] Furthermore, as cations of ionic substance B, cations represented by the following formulas (2-A) to (2-D) are also preferred.
[0103] [ka]
[0104] R in equation (2-A) 1R represents a hydrocarbon group having 4 to 10 carbon atoms (preferably a hydrocarbon group having 4 to 8 carbon atoms, more preferably a hydrocarbon group having 4 to 6 carbon atoms), and may contain heteroatoms. 2 and R 3 R represents the same or different hydrogen atom or a hydrocarbon group having 1 to 12 carbon atoms (preferably a hydrocarbon group having 1 to 8 carbon atoms, more preferably a hydrocarbon group having 2 to 6 carbon atoms, and even more preferably a hydrocarbon group having 2 to 4 carbon atoms), and may also contain heteroatoms. However, if the nitrogen atom forms a double bond with an adjacent carbon atom, 3 It does not exist.
[0105] R in equation (2-B) 4 R represents a hydrocarbon group having 2 to 10 carbon atoms (preferably a hydrocarbon group having 2 to 8 carbon atoms, more preferably a hydrocarbon group having 2 to 6 carbon atoms), and may contain heteroatoms. 5 , R 6 , and R 7 These represent, either identically or differently, a hydrogen atom or a hydrocarbon group having 1 to 12 carbon atoms (preferably a hydrocarbon group having 1 to 8 carbon atoms, more preferably a hydrocarbon group having 2 to 6 carbon atoms, and even more preferably a hydrocarbon group having 2 to 4 carbon atoms), and may also contain heteroatoms.
[0106] R in equation (2-C) 8 R represents a hydrocarbon group having 2 to 10 carbon atoms (preferably a hydrocarbon group having 2 to 8 carbon atoms, more preferably a hydrocarbon group having 2 to 6 carbon atoms), and may contain heteroatoms. 9 , R 10 , and R 11 These represent, either identically or differently, a hydrogen atom or a hydrocarbon group having 1 to 16 carbon atoms (preferably a hydrocarbon group having 1 to 10 carbon atoms, more preferably a hydrocarbon group having 1 to 8 carbon atoms), and may also contain heteroatoms.
[0107] In formula (2-D), X represents a sulfur or phosphorus atom, and R 12 , R 13 , R 14 , and R 15R represents a hydrocarbon group having 1 to 16 carbon atoms, either identical or different, (preferably a hydrocarbon group having 1 to 14 carbon atoms, more preferably a hydrocarbon group having 1 to 10 carbon atoms, even more preferably a hydrocarbon group having 1 to 8 carbon atoms, and particularly preferably a hydrocarbon group having 1 to 6 carbon atoms), and may contain heteroatoms. However, if X is a sulfur atom, R 12 It does not exist.
[0108] The molecular weight of the cation in ionic substance B is, for example, 500 or less, preferably 400 or less, more preferably 300 or less, even more preferably 250 or less, particularly preferably 200 or less, and most preferably 160 or less. It is also usually 50 or more. It is believed that the cation in the ionic substance has the property of moving towards the cathode side when a voltage is applied in the electropenetrating adhesive layer, and becoming concentrated near the interface between the electropenetrating adhesive layer and the adherend. In the embodiments of the present invention, this results in a decrease in adhesive strength after voltage application compared to the initial adhesive strength, and electropenetration occurs. Cationic substances with small molecular weights, such as 500 or less, are preferable from the viewpoint of facilitating the movement of cations towards the cathode side in the electropenetrating adhesive layer, and thus facilitating the realization of the function of decreasing adhesive strength upon voltage application.
[0109] Examples of commercially available ionic substance B include "Elexel AS-110" manufactured by Daiichi Kogyo Seiyaku Co., Ltd., "E1452", "E0599", "M2098", "M2980", "M2981", and "M2998" manufactured by Tokyo Kasei Kogyo Co., Ltd., and "BM1697" manufactured by Boron Molecular Inc.
[0110] The ionic conductivity of ionic substance B according to the embodiment of the present invention is 1.0 × 10⁻⁶. -4 mS / cm or higher is preferred. The upper limit of ionic conductivity is preferably 20 mS / cm, more preferably 15 mS / cm, even more preferably 10 mS / cm, and the lower limit is more preferably 1 mS / cm, even more preferably 3 mS / cm, and particularly preferably 5 mS / cm. The ionic conductivity of ionic substance B according to the embodiment of the present invention is 1.0 × 10 -4When it is at least mS / cm, the adhesive strength sufficiently decreases after voltage application, which is preferable. Moreover, when it is at most 20 mS / cm, the influence of weak external current is suppressed, and electrolytic peeling can be performed only when a voltage is intentionally applied, which is preferable.
[0111] The ionic conductivity is 1.0×10 -4 Examples of the ionic substance having a conductivity of not less than mS / cm include imidazolium-based, pyridinium-based, pyrrolidinium-based, and piperidinium-based substances in which the cation has a molecular weight of 160 or less, and the anion is (FSO2)2N - , (CF3SO2)2N - , Cl - , Br - , BF4 - and PF6 -Examples include combinations of these, and among them, from the viewpoint of high ionic conductivity and sufficient reduction in adhesive strength after voltage application, 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1-propyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1-butyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1-pentyl-3-methylimidazolium bis(fluorosulfonyl)imide, and 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl) are selected. Imidides, 1-propyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, and 1-pentyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide are preferred, and 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide and 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide are more preferred from the viewpoint of high availability and high ionic conductivity. Examples of commercially available ionic substances include 3-Ethyl-1-methyl-1H-imidazol-3-ium Bis(fluorosulfonyl)azanide (manufactured by Tokyo Chemical Industry Co., Ltd.) and 1-Ethyl-3-methylimidazolium Bis(trifluoromethanesulfonyl)imide (manufactured by Tokyo Chemical Industry Co., Ltd.).
[0112] In this specification, ionic conductivity can be measured, for example, by the AC impedance method using a Solartron 1260 frequency response analyzer.
[0113] In the electro-peelable adhesive composition according to the embodiment of the present invention, the content (amount blended) of ionic substance B is preferably 0.5 parts by mass or more per 100 parts by mass of polymer from the viewpoint of reducing the adhesive strength after voltage application, and preferably 30 parts by mass or less from the viewpoint of increasing the initial adhesive strength. From the same viewpoint, it is more preferably 20 parts by mass or less, even more preferably 15 parts by mass or less, particularly preferably 10 parts by mass or less, and most preferably 5 parts by mass or less. Furthermore, it is more preferably 0.6 parts by mass or more, even more preferably 0.8 parts by mass or more, particularly preferably 1.0 part by mass or more, and most preferably 1.5 parts by mass or more.
[0114] In the electro-peelable adhesive composition according to an embodiment of the present invention, the ionic substance may consist of two or more types of ionic substance A alone, or a combination of ionic substance A and ionic substance B may be used. When ionic substance A and ionic substance B are used in combination, from the viewpoint of exhibiting a function in which the adhesive strength is sufficiently reduced by the application of voltage even in a low humidity environment, it is preferable that the content of ionic substance A is 0.5 parts by mass or more and the content of ionic substance B is 0.5 parts by mass or more per 100 parts by mass of polymer. In some embodiments, the content of ionic substance A is 1 part by mass or more and the content of ionic substance B is 1 part by mass or more per 100 parts by mass of polymer, or the content of ionic substance A is 2 parts by mass or more and the content of ionic substance B is 2 parts by mass or more per 100 parts by mass of polymer. There is no particular upper limit to the content of ionic substance A and ionic substance B per 100 parts by mass of polymer, but for example, it can be 40 parts by mass.
[0115] When using two or more ionic substances in combination, it is preferable to use only ionic substance A according to the embodiment of the present invention, or to use a total of 2 to 5 types of ionic substances A and ionic substances B in combination, more preferably a total of 2 to 3 types, and even more preferably a total of 2 types.
[0116] (Other ingredients) The electrolytic adhesive composition according to the embodiment of the present invention may contain one or more components other than polymers and ionic substances (hereinafter sometimes referred to as "other components"), as necessary, to the extent that they do not impair the effects of the present invention. The other components that may be contained in the electrolytic adhesive composition according to the embodiment of the present invention will be described below.
[0117] The electrolytic adhesive composition according to the embodiment of the present invention may optionally contain a crosslinking agent for the purpose of improving creep and shear properties by crosslinking the polymer. Examples of crosslinking agents include isocyanate-based crosslinking agents, carbodiimide-based crosslinking agents, epoxy-based crosslinking agents, melamine-based crosslinking agents, peroxide-based crosslinking agents, urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, and amine-based crosslinking agents. Examples of isocyanate-based crosslinking agents include toluene diisocyanate and methylene bisphenyl isocyanate. Examples of epoxy-based crosslinking agents include N,N,N',N'-tetraglycidyl-m-xylenediamine, diglycidylaniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane and 1,6-hexanediol diglycidyl ether. If a crosslinking agent is included, the preferred content is 0.1 parts by mass or more and 50 parts by mass or less per 100 parts by mass of polymer. The crosslinking agent can be used alone or in combination of two or more types.
[0118] The electrolytic adhesive composition according to the embodiment of the present invention may optionally contain polyethylene glycol to assist in the movement of ionic substances when voltage is applied. Polyethylene glycol having a number average molecular weight of 200 to 6000 can be used. When polyethylene glycol is included, the content is preferably 0.1 parts by mass to 30 parts by mass per 100 parts by mass of polymer.
[0119] The electrolytic adhesive composition according to the embodiment of the present invention may optionally contain a conductive filler for the purpose of imparting conductivity to the electrolytic adhesive composition. The conductive filler is not particularly limited, and general known or conventional conductive fillers can be used, such as graphite, carbon black, carbon fiber, or metal powders such as silver or copper. When a conductive filler is included, the content is preferably 0.1 parts by mass or more and 200 parts by mass or less per 100 parts by mass of polymer.
[0120] The electrolytic adhesive composition according to the embodiment of the present invention may also contain various additives such as fillers, plasticizers, anti-aging agents, antioxidants, pigments (dyes), flame retardants, solvents, surfactants (leveling agents), rust inhibitors, adhesion promoters, tackifying resins, corrosion inhibitors, and antistatic agents. The total content of these components is not particularly limited as long as the effects of the present invention are achieved, but is preferably 0.01 parts by mass or more and 20 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, per 100 parts by mass of polymer.
[0121] Examples of fillers include silica, iron oxide, zinc oxide, aluminum oxide, titanium oxide, barium oxide, magnesium oxide, calcium carbonate, magnesium carbonate, zinc carbonate, pyrophyllite clay, kaolin clay, and calcined clay.
[0122] The plasticizer can be a commonly used plasticizer in general resin compositions, such as paraffin oil, process oil, liquid rubber such as liquid polyisoprene, liquid polybutadiene, and liquid ethylene-propylene rubber, tetrahydrophthalic acid, azelaic acid, benzoic acid, phthalic acid, trimellitic acid, pyromellitic acid, adipic acid, sebacic acid, fumaric acid, maleic acid, itaconic acid, citric acid, and their derivatives, dioctyl phthalate (DOP), dibutyl phthalate (DBP), dioctyl adipate, diisononyl adipate (DINA), and isodecyl succinate.
[0123] Examples of anti-aging agents include hindered phenol compounds, aliphatic and aromatic hindered amine compounds, and others.
[0124] Examples of antioxidants include butylhydroxytoluene (BHT) and butylhydroxyanisole (BHA).
[0125] Examples of pigments include inorganic pigments such as titanium dioxide, zinc oxide, ultramarine, red iron oxide, lithopon, lead, cadmium, iron, cobalt, aluminum, hydrochloride salts, and sulfates, as well as azo pigments and organic pigments such as copper phthalocyanine pigments.
[0126] Examples of rust inhibitors include zinc phosphate, tannic acid derivatives, phosphate esters, basic sulfonates, and various rust-inhibiting pigments.
[0127] Examples of adhesion promoters include titanium coupling agents and zirconium coupling agents.
[0128] Common examples of antistatic agents include quaternary ammonium salts, or hydrophilic compounds such as polyglycolic acid and ethylene oxide derivatives.
[0129] Examples of tackifying resins include rosin-based tackifying resins, terpene-based tackifying resins, phenol-based tackifying resins, hydrocarbon-based tackifying resins, ketone-based tackifying resins, as well as polyamide-based tackifying resins, epoxy-based tackifying resins, acrylic-based tackifiers (acrylic oligomers), and elastomer-based tackifying resins. These tackifying resins can be used individually or in combination of two or more types. Examples of acrylic oligomers include low molecular weight polymers of monomer components containing one or more acrylic monomers as exemplified above (for example, Mw is approximately 10 × 10 4 Less than 5 × 10 4Acrylic oligomers (less than 100 mg) can be used. Acrylic oligomers can also be obtained by polymerizing the corresponding monomer components by known methods. When producing the above oligomers by radical polymerization, polymerization initiators, chain transfer agents, emulsifiers, etc. used in radical polymerization can be added to the monomer components as appropriate, and polymerization can be carried out. The polymerization initiators, chain transfer agents, emulsifiers, etc. used in radical polymerization are not particularly limited and can be selected and used as appropriate. The weight-average molecular weight of the oligomer can be controlled by the amount of polymerization initiator and chain transfer agent used and the reaction conditions, and the amount used can be adjusted as appropriate depending on the type of these agents.
[0130] Examples of corrosion inhibitors include carbodiimide compounds, adsorption-type inhibitors, and chelate-forming metal deactivators. For example, those described in Japanese Patent Publication No. 2019-059908 can be used.
[0131] [Uses of electrolytic adhesive compositions] As described above, the electropenetrating adhesive composition according to the embodiment of the present invention exhibits the function of sufficiently reducing adhesive strength upon application of voltage, even in low-humidity environments. Due to this characteristic, the electropenetrating adhesive composition according to the embodiment of the present invention can be suitably applied to electropenetrating adhesive sheets for the applications described later. In particular, it can be preferably used for fixing components in electrical and electronic equipment.
[0132] [Initial adhesive strength, adhesive strength after voltage application, rate of decrease in adhesive strength due to voltage application] The adhesive strength of the electropenetrating adhesive layer according to the embodiment of the present invention can be evaluated by various methods, but for example, it can be evaluated by the 180° peel test described in the Examples section.
[0133] In this embodiment, the initial adhesive strength is preferably 3.0 N / cm or higher. The initial adhesive strength can be, for example, 4.0 N / cm or higher, 4.5 N / cm or higher, or 5.0 N / cm or higher. When the initial adhesive strength is 3.0 N / cm or higher, the adhesion to the adherend is sufficient, and the adherend is less likely to peel off or shift.
[0134] In this embodiment, the adhesive force (electropeeling force) after voltage application is preferably 2.0 N / cm or less. When the adhesive force after voltage application is 2.0 N / cm or less, the adherends can be separated with less force. In some embodiments, the adhesive force after voltage application is preferably 1.5 N / cm or less, and more preferably 1.0 N / cm or less. The adhesive force after voltage application can be, for example, 0.5 N / cm or less, 0.3 N / cm or less, 0.1 N / cm or less, or 0.05 N / cm or less. When the adhesive force after voltage application is 1.0 N / cm or less, it is preferable because even fragile adherends can be separated non-destructively.
[0135] In the embodiments of the present invention, the electropenetrating adhesive layer is formed as described in the Examples section, and after long-term storage in a low-humidity environment, the adhesive strength after voltage application, measured by a 180° peel test, is preferably 2.0 N / cm or less. Furthermore, in some embodiments, the adhesive strength after voltage application is preferably 1.5 N / cm or less, and more preferably 1.0 N / cm or less.
[0136] In this embodiment, the greater the difference between the adhesive strength after voltage application and the initial adhesive strength, the better the electropenetration performance. Therefore, the difference from the initial adhesive strength is preferably 3.0 N / cm or more, more preferably 4.0 N / cm or more, and even more preferably 5.0 N / cm or more.
[0137] The applied voltage is appropriately set according to the purpose and manner of use and is not limited to a specific range. The applied voltage may be, for example, 1V to 500V. In some embodiments, from the viewpoint of the safety of the worker applying the voltage, it is advantageous for the applied voltage to be 300V or less, preferably 100V or less, and more preferably 75V or less. In some embodiments, from the viewpoint of worker safety or ease of handling of the power supply, the applied voltage is preferably 50V or less, may also be 30V or less, may be 20V or less, or may be 15V or less. In some embodiments, from the viewpoint of the availability of power supplies, it is preferably 12V or less, may be 9V or less, or may be 4V or less. A low applied voltage is also preferable from the viewpoint that it enables stripping work using readily available power supplies such as dry cell batteries. Furthermore, from the viewpoint of worker safety, the lower the applied voltage, the better, but it is usually 1V or higher. In some embodiments, from the viewpoint of suppressing unintended peeling due to leakage current from electrical and electronic equipment, the applied voltage is preferably 4V or higher, but may also be 10V or higher, 20V or higher, 100V or higher, or 200V or higher.
[0138] The voltage application time is appropriately set according to the purpose and manner of use and is not limited to a specific range. The voltage application time may be, for example, 5 seconds or more and 24 hours or less. In some embodiments, from the viewpoint of work efficiency, it is advantageous for the voltage application time to be 1 hour or less, and preferably 30 minutes or less. In some embodiments, from the viewpoint of the work efficiency of the worker applying the voltage, the voltage application time is preferably 10 minutes or less, more preferably 5 minutes or less, even more preferably 3 minutes or less, preferably 1 minute or less, and may be 30 seconds or less. It is also preferable that the voltage application time is not too long, as it allows for quick peeling in the rework and recycling processes in the manufacturing process. Furthermore, from the viewpoint of work efficiency, the shorter the voltage application time, the better, but it is usually 1 second or more. In some embodiments, from the viewpoint of suppressing unintended peeling due to leakage current from electrical and electronic equipment, the voltage application time is preferably 5 seconds or more, may be 1 minute or more, may be 10 minutes or more, may be 30 minutes or more, and may be 1 hour or more.
[0139] The electrolytic adhesive composition according to the embodiment of the present invention is not particularly limited, but can be produced by appropriately stirring and mixing a polymer, an ionic substance, and additives such as a crosslinking agent, polyethylene glycol, and conductive filler, which may be added as needed.
[0140] From the viewpoint of initial adhesive strength, the thickness of the electropenetrating adhesive layer 1 is preferably 1 μm or more and 1000 μm or less. The upper limit of the thickness of the electropenetrating adhesive layer 1 is more preferably 500 μm, even more preferably 300 μm, even more preferably 200 μm, even more preferably 150 μm, even more preferably 100 μm, even more preferably 80 μm, even more preferably 70 μm, and even more preferably 60 μm. In some embodiments, the thickness of the electropenetrating adhesive layer may be 50 μm or less, or 40 μm or less. Having an electropenetrating adhesive layer that is not too thick can be advantageous from the viewpoint of thinning the electropenetrating adhesive sheet, etc. The lower limit of the thickness of the electropenetrating adhesive layer 1 is more preferably 5 μm, even more preferably 10 μm, even more preferably 20 μm, and even more preferably 30 μm. The technology disclosed herein can be preferably implemented, for example, in a manner in which the thickness of the electropenetrating adhesive layer is in the range of 20 μm to 500 μm, more preferably 30 μm to 200 μm, and more preferably 35 μm to 100 μm.
[0141] The thickness of the electro-peelable adhesive sheet according to the embodiment of the present invention is preferably 20 μm or more and 3000 μm or less. The upper limit of the thickness is more preferably 1000 μm, even more preferably 500 μm, even more preferably 300 μm, even more preferably 250 μm, even more preferably 200 μm, and even more preferably 150 μm. In some embodiments, the thickness of the electro-peelable adhesive sheet may be 120 μm or less, 100 μm or less, or 75 μm or less. Having an electro-peelable adhesive sheet that is not too thick can be advantageous from the viewpoint of thinning the bonded body, etc. The lower limit of the thickness of the electro-peelable adhesive sheet is more preferably 30 μm, and even more preferably 50 μm.
[0142] In particular, in the case of the electropenetrating adhesive sheets X1 and X2 shown in Figures 2 and 3, the thickness of the electropenetrating adhesive sheet is preferably 20 μm or more and 2000 μm or less. The upper limit of the thickness is more preferably 1000 μm, even more preferably 500 μm, even more preferably 300 μm, even more preferably 250 μm, and even more preferably 200 μm. In some embodiments, the thickness of the electropenetrating adhesive sheet may be 150 μm or less, 120 μm or less, 100 μm or less, or 75 μm or less. The lower limit of the thickness of the electropenetrating adhesive sheet is more preferably 30 μm, and even more preferably 50 μm.
[0143] In particular, in the case of the electropenetrating adhesive sheet X3 shown in Figure 4, the thickness of the electropenetrating adhesive sheet is preferably 50 μm or more and 3000 μm or less. The upper limit of the thickness is more preferably 1000 μm, even more preferably 500 μm, and the lower limit is more preferably 50 μm, even more preferably 100 μm, and even more preferably 200 μm.
[0144] The surface of the electropenetrating adhesive layer of the electropenetrating adhesive sheet according to an embodiment of the present invention, and the surface of the adhesive layer when other adhesive layers are present, may be protected by a release liner. The release liner is not particularly limited, but examples include a release liner in which the surface of a substrate (liner substrate) such as paper or plastic film is treated with silicone, and a release liner in which the surface of a substrate (liner substrate) such as paper or plastic film is laminated with a polyolefin resin. The thickness of the release liner is not particularly limited, but is preferably 10 μm or more, more preferably 20 μm or more, even more preferably 30 μm or more, preferably 100 μm or less, more preferably 80 μm or less, and even more preferably 50 μm or less.
[0145] [Method for manufacturing electro-peelable adhesive sheets] A known or conventional manufacturing method can be used for manufacturing an electropenetrating adhesive sheet according to an embodiment of the present invention. In the electropenetrating adhesive sheet according to an embodiment of the present invention, the electropenetrating adhesive layer can be formed by applying a solution of the electropenetrating adhesive composition according to the present invention dissolved in a solvent as needed onto a release liner, and then drying and / or curing it. Furthermore, if another adhesive layer is provided, the other adhesive layer can be formed by applying a solution of an adhesive composition that does not contain ionic substances dissolved in a solvent as needed onto a release liner, and then drying and / or curing it. The solvent and release liner can be those listed above.
[0146] Conventional coaters (e.g., gravure roll coaters, reverse roll coaters, kiss roll coaters, dip roll coaters, bar coaters, knife coaters, spray roll coaters, etc.) can be used for application.
[0147] By the above method, an electropenetrating adhesive layer and other adhesive layers can be manufactured, and by laminating a conductive substrate, an electropenetrating adhesive layer, and other adhesive layers as needed, an electropenetrating adhesive sheet according to an embodiment of the present invention can be manufactured.
[0148] [Method for electrolyzing off electrolyzable adhesive sheets] The peeling of the electro-peelable adhesive sheet according to the embodiment of the present invention from the adherend can be achieved by applying a voltage to the electro-peelable adhesive layer, thereby generating a potential difference in the thickness direction of the electro-peelable adhesive layer. For example, a bond in which an electro-peelable adhesive sheet X1 or X2 is attached to an adherend having a conductive adhesive surface can be peeled off by applying an electric current to the conductive layer and the conductive adhesive surface and applying a voltage to the electro-peelable adhesive layer. For example, in the case of the electropenetrating adhesive sheet X3, it can be peeled off the adherend by applying a voltage to the electropenetrating adhesive layer while energizing both conductive layers. It is preferable to apply current by connecting terminals to one end and the other end of the electrorelease adhesive sheet so that voltage is applied to the entire electrorelease adhesive layer. Note that if the adherend has a conductive adherend surface, the one end and the other end may be part of the adherend having a conductive adherend surface. Note that when peeling, water may be added to the interface between the adherend surface of the adherend having a conductive adherend surface and the electrorelease adhesive layer before applying voltage.
[0149] [Applications of electropenetrating adhesive sheets] Conventional re-peelable technologies include adhesive layers that harden and peel off by ultraviolet (UV) irradiation or adhesive layers that peel off by heat. However, electro-peelable adhesive sheets using such adhesive layers cannot be used when ultraviolet (UV) irradiation is difficult or when heat damages the adherend. The electro-peelable adhesive sheet according to the embodiment of the present invention, which is equipped with the above-mentioned electro-peelable adhesive layer, does not use ultraviolet light or heat, and can therefore be easily peeled off by applying voltage without damaging the adherend. Thus, the electro-peelable adhesive sheet according to the embodiment of the present invention is suitable for fixing secondary batteries (e.g., lithium-ion battery packs) used in mobile terminals such as smartphones, mobile phones, laptop computers, video cameras, and digital cameras to their casings.
[0150] Furthermore, examples of rigid members to be joined by the electropenetrating adhesive sheet according to the embodiment of the present invention include silicon substrates for semiconductor wafer applications, sapphire substrates, SiC substrates and metal base substrates for LEDs, TFT substrates and color filter substrates for displays, and base substrates for organic EL panels. Examples of fragile members to be joined by the double-sided electropenetrating adhesive sheet include semiconductor substrates such as compound semiconductor substrates, silicon substrates for MEMS devices, passive matrix substrates, surface cover glass for smartphones, OGS (One Glass Solution) substrates in which a touch panel sensor is attached to the cover glass, organic substrates mainly composed of silsesquioxane and organic-inorganic hybrid substrates, flexible glass substrates for flexible displays, and graphene sheets.
[0151] [zygote] An embodiment of the present invention comprises an adhesive sheet (electro-peelable adhesive sheet) according to the present invention and an adherend having a conductive adherend surface, wherein the adhesive layer (electro-peelable adhesive layer) of the electro-peelable adhesive sheet is adhered to the conductive adherend surface. Examples of adherends having a conductive surface include conductive substrates and substrates having a conductive layer. A conductive substrate may be a single layer or a laminate of conductive material. A substrate having a conductive layer may be one in which a conductive material is formed on the surface of the substrate. The description of conductive materials that can be used for conductive layer 3 above can be directly applied to conductive materials.
[0152] Examples of a bonded body according to an embodiment of the present invention include a bonded body in which an electro-peelable adhesive sheet X1 and the electro-peelable adhesive layer 1 side of the electro-peelable adhesive sheet X1 are attached to a substrate having a conductive adhesive surface, for example.
[0153] In a case where an electropenetrating adhesive sheet according to an embodiment of the present invention further comprises another adhesive layer, a second conductive substrate containing a resin component, and a second other adhesive layer, the other adhesive layer is formed on the surface of the support substrate opposite to the conductive layer, and the second conductive substrate and the second other adhesive layer are formed in this order on the surface of the electropenetrating adhesive sheet opposite to the conductive layer, and the electropenetrating adhesive layer and the second conductive substrate are in contact, another embodiment of the joint according to the embodiment of the present invention comprises an electropenetrating adhesive sheet according to an embodiment of the present invention and an adherend material, the other adhesive layer being attached to the adherend material. The adherend material is selected from conductive materials and non-conductive materials. Specific examples of non-conductive materials can be directly applied to the description of non-conductive substrates described above.
[0154] Examples of the bonded body in this embodiment include an electro-peelable adhesive sheet X1, which comprises an adherend having a conductive adhesive surface on the electro-peelable adhesive layer 1. Examples of the bonded bodies according to the embodiment of the present invention include an electro-peelable adhesive sheet X0 comprising an adherend having conductive adhesive surfaces on both sides of the electro-peelable adhesive layer 1, and an electro-peelable adhesive sheet X2 comprising an adherend having conductive adhesive surfaces on the electro-peelable adhesive layer 1 side and an adherend on the other adhesive layer 6 side. Examples of the bonded bodies according to the embodiment of the present invention include a bonded body in which the other adhesive layers 6 on both sides of the electropenetrating adhesive sheet X3 are attached to a substrate having, for example, a conductive adhesive surface, and a bonded body in which any of the other adhesive layers 6 of the electropenetrating adhesive sheet X3 are attached to a non-conductive material.
[0155] As explained above, the following matters are disclosed in this specification: <1> It contains a polymer and two or more ionic substances, An electrolytic adhesive composition wherein the ionic substance contains at least one of the following ionic substances A. (Ionic substance A) An ionic substance comprising an anion and a cation, wherein the positive charge of the cation is located on an N element not included in the cyclic structure. <2> The aforementioned ionic substance further contains at least one of the following ionic substances B: <1> The electrolytic adhesive composition described above. (Ionic substance B) An ionic substance that does not belong to the aforementioned ionic substance A. <3> The anion of the ionic substance B is at least one selected from the group consisting of bis(fluorosulfonyl)imide anions and bis(trifluoromethanesulfonyl)imide anions. <2> The electrolytic adhesive composition described above. <4> The content of ionic substance A per 100 parts by mass of the polymer is 0.5 parts by mass or more, and the content of ionic substance B is 0.5 parts by mass or more. <2> or <3> The electrolytic adhesive composition described above.
[0156] <5> <1> ~ <4> An electropenetrating adhesive sheet comprising an adhesive layer formed from any one of the electropenetrating adhesive compositions described in any one of the following. <6> <5> The adhesive sheet described above and the adherend having a conductive adhesive surface are provided. A bonded body in which the adhesive layer is attached to the conductive surface to be bonded. [Examples]
[0157] The present invention will be described more specifically below with reference to examples, but the present invention is not limited to these examples. The weight-average molecular weights below were measured by the method described above using gel permeation chromatography (GPC).
[0158] <Preparation of adhesive composition> [Example 1] Each component listed in Table 1 was stirred and mixed to obtain the electrolytic adhesive composition of Example 1. Note that the values for each component in Table 1 represent parts by mass. Furthermore, the polymer content (parts by mass) indicates the amount of solids in the polymer solution (parts by mass). The abbreviations for each component in Table 1 are as follows:
[0159] (Ionic substance A, Ionic substance B) Ionic substances were used in which the cations and anions listed below were combined as shown in Table 1. Ionic substances A and B used in the examples and comparative examples were obtained by the method described in the literature “Ionic Liquids - The Forefront and Future of Development -” [published by CMC Publishing Co., Ltd.].
[0160] • Cation 1: diallyldimethylammonium • Cation 2: Dodecyltrimethylammonium • Cation 3: Tributylmethylammonium • Cation 4: A mixture of benzyldimethyldodecylammonium, benzyldimethyltetradecylammonium, and benzyldimethylhexadecylammonium • Cation 5: Dodecylethyldimethylammonium • Cation 6: Benzyldimethyltetradecylammonium • Cation 7: Benzyltributylammonium • Cation 8: 1-ethyl-3-methylimidazolium (EMIM)
[0161] Anion 1: Bis(fluorosulfonyl)imide (FSI) Anion 2: Bis(trifluoromethanesulfonyl)imide (TFSI)
[0162] (Preparation of acrylic polymer solutions) As monomer components, 87 parts by mass of n-butyl acrylate (BA), 10 parts by mass of 2-methoxyethyl acrylate (MEA), 3 parts by mass of acrylic acid (AA), and 150 parts by mass of ethyl acetate as a polymerization solvent were placed in a separable flask and stirred for 1 hour while introducing nitrogen gas. After removing oxygen from the polymerization system in this way, 0.2 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) was added as a polymerization initiator, and the mixture was heated to 63°C and reacted for 6 hours. Subsequently, ethyl acetate was added to obtain an acrylic polymer solution with a solid content of 30% by mass. The weight-average molecular weight of the obtained acrylic polymer was 700,000. (Crosslinking agent) • V-05: Polycarbodiimide resin, product name "Carbodilite V-05", manufactured by Nisshinbo Chemical Co., Ltd.
[0163] [Examples 2-9, Comparative Examples 1-2] Except for changing the components used and their content as shown in Table 1, the electrolytic adhesive compositions of Examples 2-9 and Comparative Examples 1-2 were obtained by the same method as in Example 1.
[0164] [Table 1]
[0165] <Fabrication and evaluation of adhesive sheets and joints> Using the electrolytic adhesive compositions obtained in the examples and comparative examples, adhesive sheets and bonded structures were prepared as described below. The prepared bonded structures were also evaluated as described below. (Preparation of single-sided adhesive sheets with substrate) The electro-peelable adhesive composition obtained above was applied to the peeled surface of a polyethylene terephthalate peel liner (product name "MRF38", manufactured by Mitsubishi Chemical Corporation) using an applicator to achieve a uniform thickness. Next, it was heated and dried at 150°C for 3 minutes, and then laminated onto the peeled surface of the polyethylene terephthalate peel liner (product name "MRE38", manufactured by Mitsubishi Chemical Corporation) using a hand roller to obtain an electro-peelable adhesive layer with a thickness of 50 μm. The obtained electro-peelable adhesive layer was formed into a 20mm x 80mm sheet, the release liner (MRE38) was peeled off, and the conductive layer side of the conductive substrate was bonded to the exposed electro-peelable adhesive layer to create a single-sided adhesive sheet with the substrate attached. As the conductive substrate, aluminum foil composite PET (product name "Alpet", product number: 12-50, manufactured by Panac Co., Ltd., thickness 62μm) was used.
[0166] (Fabrication of the joint) The release liner (MRF38) of the single-sided adhesive sheet with a substrate was peeled off, and an aluminum plate (A5052) was attached to the peeled surface so that one end of the adhesive sheet protruded approximately 20 mm from the substrate. The sheet was then pressed down three times with a 2 kg roller. After that, it was left for 30 minutes in an environment of 23 ± 1 °C / 50 ± 5% RH to obtain a bonded body consisting of a conductive substrate / electropenetrating adhesive layer (adhesive sheet) / A5052.
[0167] (Initial adhesive strength) The fabricated bonded material was peeled in the direction of the arrow in Figure 5 using a peel tester (product name "Variable Angle Peel Tester YSP", manufactured by Asahi Seiko Co., Ltd.), and the adhesive strength in a 180° peel test (tensile speed: 300 mm / min, peel temperature 23 ± 1 °C, humidity 50 ± 5% RH) was measured. The initial adhesive strength was calculated according to the measurement method 1 for 180° peel adhesive strength described in JIS Z 0237 (2009). The results are shown in Table 1 as "initial adhesive strength (RT)".
[0168] (Electrolytic peeling force (normal)) Before peeling, the positive and negative electrodes of a DC current machine were attached to points α and β in Figure 5 of the bonded body, respectively. Immediately after applying a voltage of 10V for 30 seconds, the electropenetrating force (normal) was measured in the same manner as the adhesive strength measurement described above, except for the point where the bond was peeled in the direction of the arrow in Figure 5. The results are shown in Table 1 as "Electrolytic Peeling Force (RT) 10V 30s".
[0169] (Electrolytic peeling force (low humidity)) Temperature 22°C, dew point temperature -60°C, 120hr The above bonded material was stored in a dry room at a temperature of 22°C and a dew point of -60°C for 120 hours. Immediately after removal, the electropenetration force (low humidity) was measured in the same manner as the electropenetration force (normal) measurement described above. The results, expressed as "electropeeling force after low-humidity storage (10V 30s)," are shown in Table 1.
[0170] As described above, the electrolytic adhesive composition according to the example was able to exhibit the function of sufficiently reducing adhesive strength upon application of voltage even in a low-humidity environment. In contrast, the electrolytic adhesive composition according to the comparative example did not sufficiently reduce adhesive strength upon application of voltage in a normal environment and / or a low-humidity environment.
[0171] The present invention is not limited to the embodiments described above, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. [Industrial applicability]
[0172] The electropenetrating adhesive sheet of the present invention can be used, for example, to fix secondary batteries used in mobile terminals to their casings, and to join rigid or fragile members. [Explanation of Symbols]
[0173] X0, X1, X2, X3 Electro-peelable adhesive sheets 1. Electropeelable adhesive layer 3. Conductive layer 4 Supporting base material 5 Conductive base material 6. Other adhesive layers 7. Adhesion having a conductive adhesion surface 8 Laminate
Claims
1. It contains a polymer and two or more ionic substances, An electrolytic adhesive composition wherein the ionic substance contains at least one of the following ionic substances A. (Ionic substance A) An ionic substance comprising an anion and a cation, wherein the positive charge of the cation is located on an N element not included in the cyclic structure.
2. The electrolytic adhesive composition according to claim 1, wherein the ionic substance further contains at least one of the following ionic substances B. (Ionic substance B) An ionic substance that does not belong to the aforementioned ionic substance A.
3. The electrolytic adhesive composition according to claim 2, wherein the anion of the ionic substance B is at least one selected from the group consisting of bis(fluorosulfonyl)imide anions and bis(trifluoromethanesulfonyl)imide anions.
4. The electrolytic adhesive composition according to claim 2, wherein the content of the ionic substance A is 0.5 parts by mass or more per 100 parts by mass of the polymer, and the content of the ionic substance B is 0.5 parts by mass or more.
5. An electropenetrating adhesive sheet comprising an adhesive layer formed from the electropenetrating adhesive composition described in any one of claims 1 to 4.
6. The adhesive sheet described in claim 5 and the adherend having a conductive adherend surface are provided, A bonded body in which the adhesive layer is attached to the conductive surface to be bonded.
Citation Information
Patent Citations
Electrically peelable adhesive composition, electrically peelable adhesive product and method for peeling the same
JP2010037354A
Adhesive using electro-peeling composition, electro-peeling multi-layer adhesive
JP4139851B2